Ekosistem Bisnis Digital: Analisis Faktor Kesuksesan UMKM Generasi Z di Indonesia (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2026)
Digital transformation has reshaped the landscape of MSMEs in Indonesia, particularly those managed by Generation Z. This study aims to analyze key success factors of Generation Z MSMEs in building sustainable digital business ecosystems. The research employs a systematic literature review methodology by analyzing various academic sources, industry reports, and related publications from 2019-2024. Findings reveal five primary success factors: adaptive digital technology adoption, high digital literacy, social media utilization as marketing strategy, collaboration within digital ecosystems, and business sustainability orientation. Generation Z MSMEs demonstrate advantages in leveraging e-commerce platforms, digital payments, and data analytics for decision-making. Research implications provide strategic recommendations for MSME practitioners, policymakers, and stakeholders in developing ecosystems that support sustainable digital business growth, while emphasizing the importance of digital infrastructure and business mentoring aligned with digital native generation characteristics.